2012
DOI: 10.1111/j.1742-481x.2012.01109.x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, non comparative, multicenter study to investigate the effect of cadexomer iodine on bioburden load and other wound characteristics in diabetic foot ulcers

Abstract: Few studies regarding wound treatment with topical antimicrobials evaluate change in the bacterial bioburden of the wound with treatment. This study sought out to determine the in vivo effect of cadexomer iodine antibacterial dressing on diabetic foot ulcers (DFUs) that were infected or achieved a critical level of colonisation, looking specifically at wound progression in relation to bioburden. Fifteen patients corresponding to 16 total DFUs met criteria of displaying clinical signs of infection or critical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…However, with an adequately powered study, a statistically significant difference may be identified. These findings are in alignment with a previous study by Schwartz et al who used conventional culture to illustrate treatment with Cadexomer Iodine resulted in a one‐two Log10 reduction (median 0.3 Log10 reduction) in DFU bioburden …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, with an adequately powered study, a statistically significant difference may be identified. These findings are in alignment with a previous study by Schwartz et al who used conventional culture to illustrate treatment with Cadexomer Iodine resulted in a one‐two Log10 reduction (median 0.3 Log10 reduction) in DFU bioburden …”
Section: Discussionsupporting
confidence: 91%
“…The reason for excluding patients with acute clinical infection was the assumption that the behaviour of these wounds would be driven predominantly by planktonic microorganisms . Participants with contraindications to the use of Cadexomer Iodine as per the manufacturers guidelines were also excluded . Participants were randomised by coin toss on a 1:1 allocation basis to receive either two‐weeks or six‐weeks of topical antimicrobial therapy once recruited.…”
Section: Methodsmentioning
confidence: 99%
“…Several small studies have, however, demonstrated anti‐infective benefits for some antiseptic agents (eg, cadexomer iodine and hypochlorous solutions) in infected DFUs. There is evidence that dressings with silver, cadexomer iodine, and hypochlorous solutions reduce microbial load in the ulcers . The available evidence is insufficient to establish whether or not silver‐containing dressings or topical agents promote ulcer healing or prevent ulcer infection.…”
Section: Treatmentmentioning
confidence: 99%
“…There is evidence that dressings with silver, cadexomer iodine, and hypochlorous solutions reduce microbial load in the ulcers. 180,181 The available evidence is insufficient to establish whether or not silver-containing dressings or topical agents promote ulcer healing or prevent ulcer infection. To avoid promoting the development of resistance, we suggest avoid using agents topically that can also be administered systemically.…”
Section: Recommendation 27mentioning
confidence: 99%
“…15 Cadexomer iodine (CI) (Iodosorb, Smith & Nephew, Hull, UK) consists of small polysaccharide beads (cadexomer starch) containing 0.9% iodine, which causes the polysaccharide beads to swell in the presence of wound exudate, allowing a slow sustained release of iodine into the wound. [21][22][23] CI has long been used effectively in chronic wounds and is supported by many clinical studies demonstrating the removal of barriers to healing, such as microbial infection, 21,[24][25][26][27] slough/debris, 21,[28][29][30][31][32] and exudate. 21,24,27,28,31,33,34 In addition, a recent meta-analysis (Cochrane review) highlighted that CI generates higher healing rates than standard care in venous leg ulcers (VLUs).…”
mentioning
confidence: 99%